Pengaruh Kualitas Produk Dan Promosi Terhadap Keputusan Pembelian Koran Jawa Pos - Sigit Hari Prasetya (STIE Widya Manggala, 2020)
This study aims to analyze the effect of product quality and promotion on purchasing decisions. The data used in this study are primary data obtained from questionnaires. The number of samples is 100 consumers of Jawa Pos newspaper in business agents in the old city area of Central Semarang. The analysis technique used is multiple regression methods and hypothesis testing using the F test and t test. The results showed that the product quality variable had a positive and significant effect on purchasing decisions. Promotion variables have a positive and significant effect on purchasing decisions. And the variable that has the most dominant influence on purchasing decisions is the variable of product quality. From this research, the R2 value of 0.779 is obtained, which means that 77.9% of the purchasing decision variable can be explained by the product quality and promotion variables, the remaining 22.1% is explained by other variables outside the study.